High-Order Planar Bandpass Filters With Electronically-Reconfigurable Passband Width and Flatness Based on Adaptive Multi-Resonator Cascades - Roberto Gomez-Garcia (IEEE Access, 2019)
A class of quasi-elliptic-type planar bandpass filters (BPFs) with electronically controllable bandwidth between narrow-band and ultra-wideband states and enhanced passband flatness is reported. It consists of the in-series cascade of replicas of an adaptive BPF stage that exhibits three in-band poles and two transmission zeros (TZs). In this manner, BPF transfer functions with 3K poles and multiple TZs-between two K-multiplicity and 2K one-multiplicity TZs-without cross-coupling can be synthesized with a K-stage BPF architecture. Bandwidth reconfiguration is performed through the spectrally agile allocation of these TZs. Passband flattening for all the states is accomplished through the adjustment of the BPF in-band return-loss profile by tuning the external admittance inverters and those between BPF stages. The aforementioned procedures for bandwidth control and passband flattening are theoretically demonstrated with the coupling-routing diagram formalism. Furthermore, a mechanism to avoid the appearance of out-of-band spurious peaks due to the multi-stage in-series-cascade process in the associated transmission line-based BPF implementation is described. For experimental-validation purposes, a 1-GHz sixth-order varactor-tuned BPF microstrip prototype with measured flattened 1-dB referred passband-width states going from 46 to 482 MHz-measured bandwidth tuning ratio of 11.5:1-is developed and characterized. Measurements for various temperature conditions and their in situ compensation are also shown.